2017
DOI: 10.7567/apex.10.115501
|View full text |Cite
|
Sign up to set email alerts
|

Giant negative thermal expansion in Fe-doped layered ruthenate ceramics

Abstract: The effects of iron doping on the giant negative thermal expansion (NTE) of Ca2RuO4−y ceramics are investigated. Fe-doped ruthenate ceramics exhibit a large NTE even though the crystallographic unit-cell volume shows no NTE. The anisotropic thermal strain of crystal grains consumes open spaces in the sintered body and causes giant bulk volume contraction on heating. This giant NTE is reproducible against repeated thermal cycling, indicating a tough microstructure. The thermal expansion of epoxy resin is fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Data related to the warming process were collected using a laser interference dilatometer. Referred from earlier reports (Takenaka et al, 2017a,b). For comparison, data of MnCo 0.98 Cr 0.02 Ge (Zhao et al, 2015) are also shown.…”
Section: Anisotropic Thermal Expansion and Microstructural Effectsmentioning
confidence: 95%
See 4 more Smart Citations
“…Data related to the warming process were collected using a laser interference dilatometer. Referred from earlier reports (Takenaka et al, 2017a,b). For comparison, data of MnCo 0.98 Cr 0.02 Ge (Zhao et al, 2015) are also shown.…”
Section: Anisotropic Thermal Expansion and Microstructural Effectsmentioning
confidence: 95%
“…Many earlier studies have examined composites containing NTE materials, particularly β-eucryptite (Xue et al, 2010; Borrell et al, 2012) and ZrW 2 O 8 (Holzer and Dunand, 1999; Matsumoto et al, 2003; Sullivan and Lukehart, 2005; Lind et al, 2011), as thermal expansion compensating fillers. Regarding phase-transition-type giant NTE materials, composites containing Mn 3 A N (Ding et al, 2011; Takenaka et al, 2012, 2015; Takenaka and Ichigo, 2014; Lin et al, 2017), BiNi 1−x Fe x O 3 (Nabetani et al, 2015), La(Fe, Si, Co) 13 (Shan et al, 2015), and Ca 2 Ru 0.92 Fe 0.08 O 3.82 (Takenaka et al, 2017b) have been reported. Because their chemical reactivity is higher at high temperatures than those of conventional NTE materials, phase-transition-type NTE materials are difficult to use as thermal expansion compensating filler, particularly in cases of metal matrix composites (MMCs).…”
Section: Composites Containing Giant Nte Materialsmentioning
confidence: 99%
See 3 more Smart Citations